2012
DOI: 10.1179/1743132811y.0000000074
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid levels in patients with multiple sclerosis: a meta-analysis

Abstract: Our study suggests that UA is relevant to MS. Future research is needed to determine whether the administration of UA levels by inosine might be considered as a novel treatment strategy for MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
5
38
1
Order By: Relevance
“…It has been observed that MS and gout are mutually exclusive (35). It is now generally accepted that the lower serum UA level in MS patients may be due to the intrinsically reduced antioxidant capacity, as well as the increased consumption of UA in MS (11,12). The mechanisms of CNS injury during infection are complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been observed that MS and gout are mutually exclusive (35). It is now generally accepted that the lower serum UA level in MS patients may be due to the intrinsically reduced antioxidant capacity, as well as the increased consumption of UA in MS (11,12). The mechanisms of CNS injury during infection are complex.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate whether UA has diagnostic and predictive value for IM, prompted by the fact that a low UA level was found to be associated with pathological conditions such as stroke (8-10), MS (11,12,20) and CNS infections (13,14). Our research group previously investigated UA, but the focus was the association of hyperuricemia with various metabolic disorders (5-7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not include compounds that were examined in fewer than three studies such as chelation, glucosamine, selenium, and others. We also did not review compounds that had already been subjected to rigorous review and synthesis: uric acid [20][21][22] or PUFAs. 23 The largest body of research examined ALA (12 studies) and G. biloba (5 studies), with the remaining compounds having fewer than four peer-reviewed studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were 12 studies examining uric acid, we did not synthesize the findings since there are several recent reviews as well as a clinical trial completed. [20][21][22] Similarly, there is a recent Cochrane review that summarizes the literature regarding polyunsaturated fatty acids (PUFA). 23 Many compounds had fewer than three studies, which were below our threshold for synthesis; for example, chelation, polyamines, selenium, and others ( Figure 1).…”
Section: Data Extraction and Synthesismentioning
confidence: 99%